Feasibility Study of Agriculture By-Product in Removing Heavy Metals in Wastewater through Adsorption - Teoh, Wen Zhe; Hamdan, Rafidah (Recent Trends in Civil Engineering and Built Environment, 2022)
The widespread water pollution issues are becoming the major water threat in Malaysia. The ability of agricultural by-products to remove contaminants from water was investigated and reviewed in this study. Coffee waste, rice husk and mango leaves were utilized in the uptake of Cu(II) in batch experiments. The effect of pH, contact time and initial copper concentration were studied. Equilibrium data were fitted into Langmuir and Freundlich isotherm models. The data was fitted better in Langmuir isotherm with correlation coefficient of 0.8991, 0.9949 and 0.9918. The maximum adsorption capacity was 15.24, 12.30 and 15.77 mg/g on coffee waste, rice husk and mango leaves respectively which indicated the adsorption was in monolayer pattern. The results revealed that coffee waste, rice husk and mango leaves are capable to remove Cu(II) when compares with other adsorbent. The study also revealed the use of different agriculture by-products in the remediation of heavy metal and pollutants contamination in wastewater.